Dinamika Peralihan dari Kurikulum 2013 ke Kurikulum Merdeka di SDN Alalak Tengah 4 - Ramadhani, Aulia Azizah; Putra, M. Aminullah Sriyono; Mubarokati, Sari; Jariah, Siti Ainun; Pratiwi, Diani Ayu (ARZUSIN, 2025)
This research is motivated by the transition of the curriculum from the 2013 Curriculum to the Independent Curriculum at SDN Alalak Tengah 4 which faces various challenges, especially related to teacher readiness and the availability of learning resources. The purpose of the research is to identify the problems faced by schools in the curriculum transition process as well as the factors that affect the implementation of the Independent Curriculum. The method used was qualitative research with a case study approach, involving teachers and students as samples, as well as data collection through in-depth interviews with school principals and observations. The results of the study show that some teachers, especially senior teachers, have not fully understood the principles of the Independent Curriculum and have difficulties in compiling independent teaching modules. The implementation of the curriculum was carried out in stages but then fully implemented in all classes due to the pressure of competition between schools. The main obstacle is the limitation of learning media such as textbooks.